The New Pakistani Middle Class - Ammara Maqsood (India Cambridge Harvard University Press, 2017)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Note on Transliteration -- Introduction -- 1. Remembering a Modern Pakistan -- 2. Moral Rhetoric, Modernity, and Class -- 3. Piety and New Middle-Class Life -- 4. Islam and Consumption -- Conclusion -- Notes -- Bibliography -- Acknowledgments -- Index
Include Bibliography and Index
Keywords: Middle class -- Pakistan--Lahore -- Pakistan